PEMETAAN STRUKTUR BATUAN DAERAH DURIAN KAPEH KABUPATEN AGAM - Adree Octova; Dedi Yulhendra (Universitas Negeri Padang, 2016)
Iron sand spread in Indonesia still not as much as may be optimized. One of area indicated of iron sand is Durian Kapeh regions North Tiku of Tanjung Mutiara Agam Regency. Iron sand singer can be seen clearly from the outcrop. From previous studies (Mufit, 2005), in this area has more than 50% magnetic properties. It can be concluded that the potential of iron sand in this area quite potential and can be used for industrial activities later. One way for mapping of iron sand is by applying geoelectrical resistivity method with Wenner array. This array is superior in mapping laterally. Data obtained from the measurement result in form of apparent resistivity value below the sounding point. The results will be able to know the distribution of subsurface materials and can be used as reference in future mining decision. The Results of the mapping obtained the distribution of resistivity value varied from 0,0347 Ωm to 340.000 Ωm that has tended conductive properties. Rock types include iron sand, alluvial, gravel sand, silt, and basalt